Effects of physiotherapeutic intervention on motor development of children with Down Syndrome: A literature review (Research, Society and Development, 2023)
Objectives: The present study aims to describe the effects of physiotherapeutic intervention on the motor development of children with Down Syndrome. Methodology: This is a literature review, in which a search was carried out in the PubMed, PeDro, Scielo and Lilacs databases, from August to September 2022, using the descriptors early intervention/early intervention; down syndrome/down syndrome and physiotherapy/physiotherapy. Clinical trial-type studies published in the last 10 years were included, following the inclusion criteria. To evaluate the quality and level of relevance of the articles, the Jadad Scale was applied. Results: Initially, a total of 395 articles were identified. After data collection and application of the eligibility criteria, 8 articles were included. There was an improvement in muscle strength, especially in the lower limbs, balance and postural control, lung functions, core stabilization, motor coordination and the acquisition of adequate patterns. Conclusion: The study concludes that the use of physiotherapeutic interventions is effective for the motor development of children with Down Syndrome, as these interventions provide, according to the condition and needs of each child, improvements in motor development.